Implementasi Garden-Based Learning (GBL) sebagai Upaya Menumbuhkan Peduli Lingkungan dan Ketrampilan Konservasi pada Siswa - Dita Aulia Pratami; Muhimatul Umami (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
The development of Science and Technology became one of the signs of the beginning the Era of Openness, especially in the field of information. This era of openness will affect various aspects of life one of them is education. Currently, education in Indonesia experienced a serious crisis situation, especially a concern for the environment is low. Appropriate environmental science learning efforts need to be done so that awareness of environmental improvement. This study aims to inform the environment learning with Garden-Based Learning (GBL) through Eco-school to establish awareness and environmental conservation skills on students. The research method used a qualitative approach and included research type of literature study which analyzed descriptively. The result of the research showed that the application of learning of GBL through Eco-school in extracurricular activities in students is able to establish environmental awareness and conservation skills through knowledge, skill, attitude and behaviour as well towards the environment so that learning is more active, effective and meaningful.